2022
DOI: 10.1177/10775595221118933
|View full text |Cite
|
Sign up to set email alerts
|

Team Functioning and Performance in Child Advocacy Center Multidisciplinary Teams

Abstract: The quality of teamwork in Child Advocacy Center (CAC) multidisciplinary teams is likely to affect the extent to which the CAC model improves outcomes for children and families. This study examines associations between team functioning and performance in a statewide sample of CAC teams. Multidisciplinary team members ( N = 433) from 21 CACs completed measures of affective, behavioral, and cognitive team functioning. Team performance was assessed with three measures: team member ratings of overall performance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…We conducted an anonymous online survey of CAC multidisciplinary team members [ 44 ]. Each CAC has one associated multidisciplinary team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted an anonymous online survey of CAC multidisciplinary team members [ 44 ]. Each CAC has one associated multidisciplinary team.…”
Section: Methodsmentioning
confidence: 99%
“…Team processes and states may be affective (e.g., respect), behavioral (e.g., communication), or cognitive (e.g., shared goals) [33,34]. Decades of research in diverse work settings have shown that affective, behavioral, and cognitive team functioning are positively associated with team performance [32][33][34][35][39][40][41][42][43][44]. In healthcare settings, specifically, better team functioning is associated with better service quality, improved patient safety, and better clinical outcomes for those served by the team [7,45,46].…”
Section: Conceptualizing Teamwork In Relation To Implementation Outcomesmentioning
confidence: 99%
“…Stronger partnerships supported a higher level of team functioning which led to more individuals receiving access to needed supports. McGuier et al's (2022) findings substantiate the need for collaboration among community partners to support information sharing, decision-making, coordinated case planning, and ensuring youth with PSBs get access to needed services.…”
Section: Community Partnersmentioning
confidence: 53%
“…Training community partners in the dynamics of youth with PSB and the effectiveness of evidence-informed interventions is of great importance in cultivating stakeholder relationship and gaining buy-in to evidence-based practices (Sites & Widdifield, 2020). McGuier et al (2022) found a correlation between strong team member partnerships and better outcomes for children and families. Their research demonstrated correlations between team member perspectives related to team functioning and referrals for mental health treatment.…”
Section: Community Partnersmentioning
confidence: 91%
See 1 more Smart Citation